Got to be something here : the rise of the Minneapolis sound - Swensson, Andrea (University of Minnesota Press, 2017)
Beginning in the year of Prince's birth, 1958, with the recording of Minnesota's first R & B record by a North Minneapolis band called the Big Ms, Got to Be Something Here traces the rise of that distinctive sound through two generations of political upheaval, rebellion, and artistic passion. Funk and soul become a lens for exploring three decades of Minneapolis and St. Paul history as longtime music journalist Andrea Swensson takes us through the neighborhoods and venues, and the lives and times, that produced the Minneapolis Sound. Visit the Near North neighborhood where soul artist Wee Willie Walker, recording engineer David Hersk, and the Big Ms first put the Minneapolis Sound on record. Across the Mississippi River in the historic Rondo district of St. Paul, the gospel-meets-R & B groups the Exciters and the Amazers take hold of a community that will soon be all but erased by the construction of I-94. From King Solomon's Mines to the Flame, from The Way in Near North to the First Avenue stage (then known as Sam's) where Prince would make a triumphant hometown return in 1981, Swensson traces the journeys of black artists who were hard-pressed to find venues and outlets for their music, struggling to cross the color line as they honed their sound. And through it all, there's the music: blistering, sweltering, relentless funk, soul, and R & B from artists like Maurice McKinnies, Haze, Prophets of Peace, and The Family, who refused to be categorized and whose boundary-shattering approach set the stage for a young Prince Rogers Nelson and his peers Morris Day, Andre Cymone, Jimmy Jam, and Terry Lewis to launch their careers, and the Minneapolis Sound, into the stratosphere. A visit to Prince's Paisley Park and a conversation with the artist provide a rare glimpse into his world and an intimate sense of his relationship to his legacy and the music he and his friends crafted in their youth.